Toward Eco-centric, Earth-as-School, and Love-based Curriculum and Learning: Example of a graduate course - Kaur, H.; Khant, M.; Kistner, S.; McHugh, D.; Yu, W.; Moraga-Prieto, C.; Pax Andebo, P.; Lin, J. (South African Journal of Higher Education, 2023)
This article puts forward love, care, and reverence for all people and our nonhuman kin as the center of posthumanist education. Opening our spiritual eye and building intimate relationships with nature and with all elements of the universe is envisioned as part of a schooling or post-schooling experience; our body, heart and spirit, along with our mind, is an essential part of learning. The article describes the experiences of students taking a graduate level course focusing on global climate change and education at a university in the United States. We use the course as an example to explore what posthumanist education entails. In this qualitative study, students taking the course, along with the faculty designing and teaching the course, describe the course curriculum and pedagogies and reflect on the course’s impact on them. Data sources include the syllabus, students’ reflection papers, nature contact journals, final projects, art works, and group conversations. Although situated in North America, the article is rich with international perspectives as student authors came from six different countries. The article posits that posthumanist education must be eco-centric and love-based, engaging students’ whole being to feel for and love Mother Nature. Keywords: curriculum, education, nature, posthumanism, climate change, higher education, teaching and learning, contemplative pedagogies, spirituality